Where has War For Harts and Souls Gone?, America and the Liberals in Yugoslavia in 1960' and early 1970' - Jakovina, Tvrtko (Array, 2008)
Author briely analyzed the importance of the Prague Spring in 1968 for the overall standing of Tito's Yugoslavia. By confronting documents of the Croatian emigre association form Cleveland and some of the classifie analyses of the State Department files, the difference between the US public and secret diplomacy vis-a-vis Yugoslavia is stressed. The autor argues that Washington was intereseted only in the unity of Yugoslavia and the independence form the Soviet Union, not hte liberalization and democratization.